Penegakan Hukum yang Dilakukan oleh Kejaksaan Terhadap Pemberantasan Tindak Pidana Korupsi - Idrak, Rachmat (Sovereign: International Journal of Law, 2023)
This study aims to analyze the law enforcement carried out by the Makassar District Attorney in eradicating corruption, and the factors that influence it. This type of research is empirical legal research with a quantitative descriptive in nature. This research was conducted at the Makassar District Attorney’s Office. The data collection techniques used in this study were questionnaires, documentation, and literature study. The data analysis technique used is quantitative data analysis techniques. The results showed that law enforcement carried out by the Makassar District Attorney in eradicating corruption is by conducting investigations and prosecutions. However, in enforcement, his party still has to coordinate with the Corruption Eradication Commission. Factors affecting law enforcement carried out by the Makassar District Attorney’s Office in eradicating corruption are legal structure factors, legal culture factors, and community legal awareness factors. It is hoped that the Makassar District Attorney’s Office will be more professional in investigating and prosecuting corruption crimes.